Cellulose film, manufacturing method thereof, and dehumidifying membrane comprising the same

KR103019967B1Active Publication Date: 2026-09-15KOREA INST OF ENERGY TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
KR1020230096725
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-07-25
Publication Date
2026-09-15
Estimated Expiration
2043-07-25

Smart Images

  • Figure 112023081916970-PAT00005_ABST
    Figure 112023081916970-PAT00005_ABST
Patent Text Reader

Abstract

The method for manufacturing a cellulose film according to the present invention is designed to solve the problems of complex modification processes in the past and to improve the inadequate physical properties of dehumidifying film materials. It relates to a method for manufacturing a cellulose film that has a uniform surface and excellent mechanical properties, exhibits minimal degradation of properties upon contact with water, and demonstrates excellent water vapor adsorption rate, permeability, and selectivity through a water-based system, a low-temperature drying process, and solvent annealing. The method for manufacturing a cellulose film according to one embodiment offers high efficiency and economic advantages in that it utilizes inexpensive general-purpose raw materials and involves a simple process.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a cellulose film, a method for manufacturing the same, and a dehumidifying film comprising the same. Specifically, the invention relates to a method for manufacturing a cellulose film having a uniform surface and excellent mechanical properties through an aqueous system, a low-temperature drying process, and solvent annealing. Background Technology

[0003] Cellulose derivatives can be classified into cellulose ethers, cellulose esters, etc., depending on the chemical processing method, and based on their diverse physical properties, they are used in a wide range of industrial fields such as fibers, films, photographic films, glass substitutes, paint binders, paper pastes, adhesives, defoaming agents, detergents, synthetic resins, and the food industry.

[0004] The most common example of the above-mentioned cellulose derivative is Carboxymethyl Cellulose (CMC), a cellulose ether. Unlike cellulose, which is insoluble in water, CMC is water-soluble and can be mass-produced, offering economic advantages. Based on these advantages, it is used in various forms in the fields of pharmaceuticals, cosmetics, food, and industry. However, CMC has the disadvantage of having inferior mechanical properties, such as tensile strength, compared to cellulose acetate or other naturally derived polymers.

[0005] Furthermore, various methods for modifying cellulose to improve its nano-scale or physical properties are being studied; for instance, oxidized nanocellulose can be produced by TEMPO treatment. However, since this TEMPO treatment process involves complex steps such as raw material processing, precipitation, filtration, and purification, it requires simplification compared to conventional methods due to issues regarding operational efficiency, economic feasibility, and yield.

[0006] Furthermore, when using general polymer film manufacturing methods, such as solution casting, to form hydrophilic cellulose into a film, a problem arises where solubility decreases during the drying process at high temperatures above the boiling point of the solvent, making it difficult to form a uniform film.

[0007] Meanwhile, problems such as corrosion and freezing occur due to the water vapor included in the carbon dioxide capture process from flue gas generated at thermal power plants. To address this, new dehumidification membrane materials are being developed to separate water vapor from flue gas. Generally, hydrophilicity and crystallinity are controlled to improve water vapor permeability and selectivity. However, methods for controlling hydrophilicity and crystallinity are complex and difficult, making commercialization challenging. Furthermore, most polymers currently being developed on a laboratory scale for water vapor separation consist of hydrophilic functional groups applied to hydrophobic polymers or have structures of hydrophilic-hydrophobic copolymers; these have disadvantages such as high costs and unstable structures characterized by clear phase separation between hydrophobic and hydrophilic regions. Additionally, films with enhanced hydrophilicity to increase water vapor selectivity still face the problem of reduced mechanical strength when exposed to water due to their high hydrophilicity.

[0008] Therefore, there is an urgent need for research and development on dehumidification membrane materials that can be manufactured using inexpensive raw materials and simple processes, exhibit a small decrease in mechanical strength when exposed to water, and enable dehumidification from mixed gases containing water vapor even at low relative humidity. The problem to be solved

[0010] The objective of the present invention, which is to solve the problems of the past, is to provide a method for manufacturing a cellulose film that has a uniform surface and allows for easy control of hydrophilicity and crystallinity through a simple process.

[0011] In addition, another objective of the present invention is to provide a cellulose film having excellent mechanical properties, a small decrease in mechanical strength when exposed to water, and capable of dehumidifying even in mixed gases with low relative humidity of 20% or less, and a dehumidifying film containing the same. means of solving the problem

[0013] The inventors of the present invention completed the present invention by discovering, through continuous research to achieve the above-mentioned objectives, that when an aqueous solution containing a cellulose ether derivative is formed into a film through a low-temperature drying process, followed by an esterification reaction process and a solvent annealing step, a uniform and transparent cellulose film exhibiting excellent tensile strength can be obtained, and furthermore, the film has significantly improved water vapor adsorption rate, permeability, and selectivity. At the same time, this manufacturing method is superior to conventional technology in terms of economic advantages and work efficiency by using general-purpose raw materials and involving a simple process.

[0014] The present invention provides a method for manufacturing a cellulose film comprising: (a) a step of manufacturing a cellulose ether film by casting an aqueous solution containing a cellulose ether derivative; (b) a step of manufacturing a cellulose ester film by esterifying the cellulose ether film; and (c) a step of solvent annealing the cellulose ester film.

[0015] According to one embodiment of the present invention, step (c) may involve impregnating the cellulose ester film with an alcohol-based solvent.

[0016] According to one embodiment of the present invention, the alcohol-based solvent may be one or more combinations selected from monohydric alcohols, dihydric alcohols, and trihydric alcohols.

[0017] According to one embodiment of the present invention, the alcohol-based solvent is C 1-7 It can be a monohydric alcohol.

[0018] According to one embodiment of the present invention, after step (c), a step of drying at a temperature of ±5°C of the boiling point of the solvent may be further included.

[0019] According to one embodiment of the present invention, step (a) may be performed at a temperature of 40°C or lower.

[0020] According to one embodiment of the present invention, the aqueous solution may further comprise a polyfunctional compound containing at least one carboxyl group.

[0021] According to one embodiment of the present invention, the polyfunctional compound may contain at least one carboxyl group and at least one amino group.

[0022] According to one embodiment of the present invention, the esterification reaction may be performed at a temperature of 150°C or higher.

[0023] According to one embodiment of the present invention, step (b) may involve contacting a cellulose ether film with a reaction solution comprising a polyfunctional compound containing at least one carboxyl group and a solvent to perform an esterification reaction.

[0024] According to one embodiment of the present invention, the aqueous solution and the reaction solution may each independently further include a polar solvent.

[0025] According to one embodiment of the present invention, the cellulose ether derivative is C 1-7 Alkyl cellulose, hydroxy C 1-7 Alkyl cellulose and carboxy C 1-7 It may be one or more combinations selected from alkyl cellulose, etc.

[0026] According to one embodiment of the present invention, the contact angle of the cellulose ester film with respect to water may be greater than that of the cellulose ether film.

[0027] The present invention can provide a cellulose film manufactured according to the method for manufacturing a cellulose film described above.

[0028] According to one embodiment of the present invention, the cellulose film may have a breaking tensile strength of 60 MPa or more and an elongation of 10% or more, measured according to ASTM D882 under a thickness condition of 80 ± 2 μm.

[0029] According to one embodiment of the present invention, the water vapor adsorption rate of a cellulose film with a thickness of 80±2㎛ at 75% relative humidity may be 2% or more.

[0030] According to one embodiment of the present invention, the water vapor (H2O) / nitrogen (N2) selectivity of a cellulose film with a thickness of 80±2㎛ at 30% relative humidity may be 1,500 or more.

[0031] According to one embodiment of the present invention, the water vapor permeability of a cellulose film with a thickness of 80±2㎛ at 15% relative humidity may be 100,000 Barrer or more.

[0032] The present invention can provide a dehumidifying film comprising the cellulose film described above. Effects of the invention

[0034] The method for manufacturing a cellulose film according to the present invention is designed to solve the problems of complex modification processes in the past and to improve the inadequate physical properties of dehumidifying film materials. It relates to a method for manufacturing a cellulose film that has a uniform surface and excellent mechanical properties, exhibits minimal degradation of properties even when in contact with water, and demonstrates excellent water vapor adsorption rate, permeability, and selectivity through a water-based system, a low-temperature drying process, and solvent annealing. The method for manufacturing a cellulose film according to one embodiment has the advantages of economic benefits and high process efficiency in that it allows for the control of the hydrophilicity and crystallinity of the cellulose film through a simple process, utilizes inexpensive general-purpose raw materials, and is simple.

[0035] In particular, unlike other dehumidifying membrane materials that apply hydrophilic functional groups to conventional hydrophobic polymers, the cellulose film of the present invention is a material synthesized by modifying a polymer that exhibits hydrophilicity; therefore, the inherent water vapor separation characteristics of the polymer can be exhibited even in low-humidity environments, and thereby, in the case of a dehumidifying membrane containing the cellulose film, excellent water vapor separation performance can be achieved even in actual low-humidity processes such as flue gas and electrochemical reactions. Brief explanation of the drawing

[0037] FIG. 1 is a schematic diagram briefly illustrating the hydration reaction of an alcohol solvent in the method for manufacturing a cellulose film according to Example 1 of the present invention. Figure 2 shows XRD measurement data of films according to Example 1, Comparative Examples 1 and 2. Figure 3 shows the contact angle of the film with respect to water according to Example 1, Comparative Examples 1 and 2. FIG. 4 is a stress-strain curve graph showing the results of measuring the tensile strength (stress) and elongation (strain) of the cellulose films according to Example 1, Comparative Examples 1 and 2 of the present invention. Figure 5 is a graph of the hysteresis results of the water vapor adsorption rate measurement process of the films according to Example 1, Comparative Examples 1 and 2. Figure 6 is a graph showing the measurement results of water vapor adsorption rates according to relative humidity of films according to Example 1, Comparative Examples 1 and 2. Figure 7 is a graph of the water vapor permeability measurement results of films according to Example 1, Comparative Examples 1 and 2. Specific details for implementing the invention

[0038] The present invention will be described in more detail below through specific examples or embodiments, including the attached drawings. However, the following specific examples or embodiments are merely references for the detailed description of the present invention and the present invention is not limited thereto and may be implemented in various forms.

[0039] Furthermore, unless otherwise defined, all technical and scientific terms have the same meaning as generally understood by one of the art to which the present invention pertains. The terms used in the description of the present invention are merely for the purpose of effectively describing specific embodiments and are not intended to limit the present invention.

[0040] Additionally, the singular form used in the specification and the appended claims may be intended to include the plural form unless specifically indicated otherwise in the context.

[0041] Additionally, units used herein without special mention are based on weight, for example, units of % or ratio mean weight % or weight ratio, and weight % means the weight percentage of any one component of the total composition that occupies the composition, unless otherwise defined.

[0042] Furthermore, when a part in this specification is described as "comprising" a certain component, this means that, unless specifically stated otherwise, it does not exclude other components but may include additional components.

[0043] Additionally, the numerical ranges used in this specification may include lower and upper limits and all values ​​within the range, increments logically derived from the form and width of the defined range, all of which are limited values, and all possible combinations of upper and lower limits of numerical ranges defined in different forms. Unless otherwise specifically defined in the specification of this invention, values ​​outside the numerical range that may occur due to experimental error or rounding of values ​​are also included in the defined numerical range.

[0044] Hereinafter, a method for manufacturing a cellulose film according to one embodiment of the present invention will be described in more detail.

[0045] The present invention provides a method for manufacturing a cellulose film comprising: (a) a step of manufacturing a cellulose ether film by casting an aqueous solution containing a cellulose ether derivative; (b) a step of manufacturing a cellulose ester film by esterifying the cellulose ether film; and (c) a step of solvent annealing the cellulose ester film.

[0046] According to one embodiment of the present invention, step (a) is a step of preparing an aqueous solution by dissolving a cellulose ether derivative in water. Accordingly, the method for manufacturing a cellulose film according to one embodiment can manufacture the film by applying an aqueous system, unlike conventional methods that use a solvent other than water.

[0047] According to one embodiment of the present invention, the cellulose ether derivative may be used without significant limitation if it is a derivative in which the -OH (hydroxy) of the cellulose backbone is substituted with -OR (substituted or unsubstituted alkoxy).

[0048] Specifically, the degree of substitution (DS) of the cellulose ether derivative may be 0.3 or higher, 0.4 or higher, 0.5 or higher, 0.8 or higher, 1.0 or higher, or 1.4 or higher, but is not significantly limited as long as the cellulose ether derivative is within a range of water solubility. The upper limit is not significantly limited, but may be 3.0 or lower. Here, the degree of substitution may be measured in accordance with ASTM D 1439, and the degree of substitution refers to the number of substituents included within a single glucose repeating unit constituting the cellulose.

[0049] The degree of crystallization of the above cellulose ether derivative may be 20% or more, 30% or more, but is not limited thereto, and the upper limit may be 50% or less, although the upper limit is not specifically limited. The degree of crystallization may be measured using a powder X-ray diffraction measuring device and may be measured according to a method known in the art for measuring the degree of crystallization of polymers.

[0050] The weight average molecular weight (Mw) of the above cellulose ether derivative may be 1,000 to 5,000,000 Da, specifically 10,000 to 3,000,000 Da, but is not limited thereto.

[0051] The average diameter of the powder of the above cellulose ether derivative may be 1 nm to 50 μm, specifically 5 nm to 10 μm, more specifically 1 μm or less, but is not limited thereto.

[0052] According to one embodiment of the present invention, the cellulose ether derivative is C 1-7 Alkyl cellulose, hydroxy C 1-7 Alkyl cellulose and carboxy C 1-7 It may be one or more combinations selected from alkyl cellulose, etc. Non-limiting examples of the cellulose ether derivatives include methyl cellulose (MC), ethyl cellulose (EC), methyl ethyl cellulose (MEC), carboxymethyl cellulose (CMC), carboxymethyl ethyl cellulose (CMEC), hydroxyethyl cellulose (HEC), hydroxypropyl cellulose (HPC), hydroxyethyl methyl cellulose (HEMC), hydroxypropyl cellulose (HPC), and hydroxypropyl methyl cellulose (HPMC), and more specifically, methyl cellulose (MC) and ethyl cellulose (EC) may be used.

[0053] According to one embodiment of the present invention, the aqueous solution may contain 0.1 to 50 weight%, specifically 1 to 30 weight%, more specifically 3 to 15 weight% of the cellulose ether derivative, but is not limited thereto.

[0054] According to one embodiment of the present invention, the aqueous solution may further comprise a polar solvent. The polar solvent may be used without significant limitation as long as it is a solvent that is miscible with water, and may be a polar protic solvent or a polar aprotic solvent. As an example, C 1-7 Alcohols (methanol, ethanol, etc.) or THF, etc. may be used. Specifically, the polar solvent may have a boiling point lower than that of water, and may be 90°C or lower, specifically 80°C or lower, more specifically 75°C or lower, but is not limited thereto. The water to polar solvent may satisfy a weight ratio of 1 to 9:9 to 1, specifically 5 to 9:5 to 1, but is not limited thereto.

[0055] According to one embodiment of the present invention, the aqueous solution may further comprise a polyfunctional compound. The polyfunctional compound may contain at least one carboxyl group, specifically two or more carboxyl groups, or at least one carboxyl group and at least one amino group. The polyfunctional compound may subsequently participate in an esterification reaction with a cellulose ether film in step (c).

[0056] Specifically, as an example of the above-mentioned polyfunctional compound, C including succinic acid, maleic acid, fumaric acid, malic acid, and tartaric acid, etc. 1-30 Dicarboxylic acids of; C including citric acid, etc. 1-30 Tricarboxylic acids of; C including glycine, alanine, serine, threonine, valine, leucine, isoleucine, aspartic acid, and glutamic acid, etc. 1-30C, including aminocarboxylic acids, glutamine, and oxamic acid, etc. 1-30 Examples include amide carboxylic acids, but are not limited to these.

[0057] According to one embodiment of the present invention, the polyfunctional compound may be included in an amount of 1 to 80 parts by weight, specifically 10 to 60 parts by weight, more specifically 15 to 40 parts by weight, with respect to 100 parts by weight of the cellulose ether derivative, but is not limited thereto.

[0058] According to one embodiment of the present invention, the casting process of step (a) may be performed at a temperature below the boiling point of the aqueous solution, unlike conventional methods. Specifically, the drying may be performed at a temperature of 50°C or lower, more specifically at 40°C or lower, or, without limitation, at a temperature of 0°C or higher or 5°C or higher.

[0059] According to another embodiment, if the aqueous solution further comprises a polyfunctional compound, the prepared cellulose ether film may also comprise a polyfunctional compound.

[0060] According to one embodiment of the present invention, step (b) is a step of producing a cellulose ester film by esterifying the cellulose ether film produced in step (a).

[0061] According to one embodiment of the present invention, if the cellulose ether film does not contain a polyfunctional compound, step (b) may involve contacting the cellulose ether film with a reaction solution containing a polyfunctional compound and a solvent to perform an esterification reaction. Specifically, the cellulose ether film may be contacted with the reaction solution, and then the film wetted with the reaction solution may be subjected to an esterification reaction.

[0062] A detailed description of the polyfunctional compound is omitted as it is the same as described above. Specifically, the reaction solution may contain the polyfunctional compound in an amount of 0.1 to 30 wt / v (weight / volume)%, specifically 1 to 25 wt / v%, and more specifically 2 to 15 wt / v%. In addition, the solvent may use one or more combinations selected from water, non-polar solvents, and polar solvents. Conventional or known materials may be used for the non-polar solvent, and the polar solvent is omitted as it is the same as described above. Furthermore, the method of contacting the cellulose ether film with the reaction solution may use known methods such as immersion, dropping, coating, or spraying, and the contact may be performed for at least 1 hour, preferably at least 2 hours.

[0063] According to another embodiment of the present invention, if the cellulose ether film prepared in step (a) contains a polyfunctional compound, step (b) may involve directly esterifying the cellulose ether film.

[0064] [Reaction Equation]

[0065]

[0066] According to one embodiment of the present invention, the esterification reaction may be performed at a temperature of 130°C or higher, specifically 150°C or higher. Specifically, as shown in the reaction scheme above, the esterification reaction is performed on the -OR of the cellulose ether film (wherein R is a substituent of the repeating unit of the cellulose ether derivative, specifically hydrogen, C 1-7 Alkyl, Hydroxy C 1-7 Alkyl and carboxylic acid 1-7In the case of one or more selected from alkyls, a hydroxyl group in which R is H is substituted with a carboxyl group of the polyfunctional compound (XR'COOH, where X is a functional group of the polyfunctional compound) by esterifying with the carboxyl group to form -O(C=O)R'X (ester), thereby producing a cellulose ester film. Additionally, in the -O(C=O)R'X of the produced cellulose ester film, R' is C 1-10 C in which an alkylene or methylene group is substituted with O, C(=O), NH, S(=O), C(=O)O, or NHCO 1-10 It may be an alkylene group, and X may be a carboxyl group or an amino group, but is not limited thereto. Furthermore, if X is a carboxyl group, the form of the salt (-COO - M + , here M + In that it is not a metal cation, resistance to water can be further improved.

[0067] Specifically, the degree of substitution (DS) of the cellulose ester film may be 0.01 or higher, 0.02 or higher, 0.03 or higher, 0.04 or higher, or 0.05 or higher, but is not limited thereto. The upper limit is not strictly limited, but may be 2.0 or lower. Here, the degree of substitution refers to a solid 13 It can be analyzed based on C NMR spectra, but is not limited thereto, and can be measured according to other known methods. In addition, the degree of ester substitution can be easily controlled through reaction conditions, such as the esterification reaction time and the concentration of the polyfunctional compound, in order to produce a cellulose film with the desired properties.

[0068] According to one embodiment of the present invention, the contact angle (θ1) with water of the prepared cellulose ester film may be greater than the contact angle (θ2) with water of the cellulose ether film (θ1 > θ2), specifically 1.1 times or more (θ1 > 1.1 * θ2) and 2 times or less (θ1 < 2 * θ2).

[0069] According to one embodiment of the present invention, step (c) may involve impregnating the cellulose ester film with an alcohol-based solvent. As shown in FIG. 1, the alcohol-based solvent reacts with the ester portion of the cellulose ester film to undergo a hydration reaction, which can change the form of hydrogen bonding of the cellulose functional groups, thereby allowing for the control of hydrophilicity and crystallinity. When the attractive forces between or within cellulose chains change, polymer characteristics such as crystallinity and hydrophilicity also change. When the cellulose film is impregnated with an alcohol-based solvent, the form of hydrogen bonding of the cellulose functional groups changes as shown in FIG. 1. Consequently, as seen in the XRD data comparing the sizes of the crystalline and amorphous regions in FIG. 5, crystallinity increases significantly. Additionally, as shown in FIG. 6, it was confirmed that a change in hydrophilicity occurred by checking the water contact angle on the film surface. In particular, the cellulose ester film that has been processed only up to step (b) above exhibits low water vapor permeability in the low-humidity region, and to solve this, excellent water vapor permeability and selectivity can be achieved by performing a solvent annealing step.

[0070] According to one embodiment of the present invention, the alcohol-based solvent may be one or more combinations selected from monohydric alcohols, dihydric alcohols, and trihydric alcohols. Specifically, the alcohol-based solvent is C 1-7The alcohol-based solvent may be a monohydric alcohol. More specifically, the alcohol-based solvent may be any one or more combinations selected from the group consisting of 2-methoxyethanol, 2-ethoxyethanol, 2-propoxyethanol, 2-butoxyethanol, 1-methoxy-2-propanol, 1-ethoxy-2-propanol, 1-propoxy-2-propanol, methanol, ethanol, n-propanol, isopropanol, 1-butanol, 2-butanol, etc., but is not limited thereto. Preferably, the alcohol-based solvent may be methanol.

[0071] According to one embodiment of the present invention, step (c) can be performed for 1 hour or more, 6 hours or more, or 10 hours or more, and can be used without significant limitation as long as the method allows the alcohol-based solvent to come into contact with all surface areas of the cellulose ester film in addition to impregnation.

[0072] According to one embodiment of the present invention, after step (c), a drying process may be further performed, and specifically, the drying process may be performed at a temperature of ±5°C of the boiling point of the solvent. It is preferable to perform the drying process for at least 1 hour, at least 3 hours, at least 6 hours, or at least 10 hours until all the solvent evaporates, thereby enabling the production of a cellulose film exhibiting excellent water vapor permeability and selectivity in a low-humidity region.

[0073] The present invention can provide a cellulose film manufactured according to the method for manufacturing a cellulose film described above. The thickness of the cellulose film can be easily controlled according to manufacturing process conditions such as the concentration of the aqueous solution and the coating thickness, and can be manufactured with a thickness in a wide range from 1 nm to 50 mm.

[0074] According to one embodiment of the present invention, the cellulose film may have a breaking tensile strength measured according to ASTM D882 at room temperature and a thickness of 80±2㎛, which is 55 MPa or more, 60 MPa or more, or 65 MPa or more, and 200 MPa or less, although the upper limit is not particularly limited. In addition, the elongation may be 10% or more or 15% or more, and may be 50% or less, although the upper limit is not particularly limited.

[0075] According to one embodiment of the present invention, the cellulose film may have a tensile strength at break measured according to ASTM D882 at room temperature and a thickness of 80±2㎛, which may decrease by 20% or less, 15% or less, 13% or less, or 1% or more compared to the value before contact with water. The cellulose film has the advantage that, even when in contact with water, a rapid deterioration of physical properties does not occur compared to conventional technology.

[0076] According to one embodiment of the present invention, the water vapor adsorption rate of a cellulose film with a thickness of 80±2㎛ at room temperature and 75% relative humidity may be 2% or more, 5% or more, 8% or more, or 9% or more, and the upper limit may be 20% or less, although the upper limit is not particularly limited.

[0077] According to one embodiment of the present invention, the water vapor (H2O) / nitrogen (N2) selectivity of a cellulose film with a thickness of 80±2㎛ at room temperature and 30% relative humidity may be 1,000 or more, 1,200 or more, or 1,500 or more, and the upper limit may be 5,000 or less, although the upper limit is not particularly limited.

[0078] According to one embodiment of the present invention, at room temperature, relative humidity of 15 to 90%, or relative humidity of 15%, the water vapor permeability of a cellulose film with a thickness of 80±2㎛ may be 80,000 Barrer or more, 100,000 Barrer or more, 120,000 Barrer or more, 150,000 Barrer or more, or 200,000 Barrer or more, and the upper limit may be 1,000,000 Barrer or less, although the upper limit is not particularly limited.

[0079] The present invention can provide a dehumidifying film comprising the cellulose film described above.

[0080] The present invention will be explained in more detail below based on the following examples and comparative examples. However, the following examples and comparative examples are merely illustrative of the present invention and are not intended to limit the present invention.

[0081] [Physical Property Evaluation Methods]

[0082] 1) Degree of Ester Substitution (DS): The degree of ester substitution of a cellulose ester film is solid 13 Intensity of the peak derived from the cellulose ether derivative framework in the C NMR spectrum (I CEL ) and intensity of substituent-derived peaks (I AC It was calculated using the following formula using ).

[0083] [Substitution Degree (DS)] =

[0084] -I CEL : Peak intensity derived from cellulose ether derivative skeleton (103 ppm)

[0085] -I AC : Peak intensity derived from ester substituents (33 ppm)

[0086] -n CEL : Number of carbon atoms in the cellulose ether derivative group

[0087] -n AC: Number of carbon atoms in the ester substitution group

[0088] 2) Contact angle (°): 10 μl of distilled water and a droplet analyzer (DSA 100 instrument from KRUSS, Hamburg, Germany) were used. Distilled water was dropped onto the surface of the cellulose film prepared through the examples and comparative examples, and the contact angle after 10 seconds was measured and is shown in Table 1 and Figure 3 below.

[0089] 3) Tensile Strength at Break [MPa], Elongation [%]: The tensile strength and elongation at break of the cellulose films (dry) (thickness: approximately 80 μm) prepared through the examples and comparative examples were measured according to ASTM D638 and are shown in Table 1 and Figure 2 below. In addition, to form a wet state of the prepared cellulose films, they were left for 2 hours under conditions of 90% relative humidity, and then the tensile strength and elongation at break were measured under the same conditions as above and are shown in Figure 4.

[0090] 4) Water vapor adsorption rate (%) by relative humidity

[0091] Cellulose films prepared through the examples and comparative examples are of a certain size (1x1 cm 2 After cutting, the mass was measured at different relative humidity levels inside a DVS chamber maintained at 35°C. Measurements were taken by gradually increasing the relative humidity from 0% to 90% and then gradually decreasing it to 0%. For each relative humidity level, the percentage of the mass at 0% relative humidity was calculated relative to the mass of the saturated film. Hysteresis, which is the difference between adsorbed and desorbed water vapor, was observed, and the results are shown in Fig. 5. Additionally, the water vapor adsorption rate at 75 RH% relative humidity is shown in Table 1 and Fig. 6 below.

[0092] 5) Water vapor transmittance and water vapor (H2O) / nitrogen (N2) selectivity according to relative humidity

[0093] The water vapor permeability of the cellulose films prepared through the examples and comparative examples was measured according to ASTM E96-66 (upright cup method). Specifically, a Panye cell to be used in the experiment was filled with a solid desiccant, and then the cellulose film was fixed and sealed on top of it, followed by measuring the initial mass of the cell. The experiment was conducted inside a DVS chamber capable of continuously controlling and measuring temperature, relative humidity, and mass. Using the dry cup method, the increase in mass as water vapor permeated from the chamber into the cup according to humidity was measured, and the water vapor permeability was calculated by calculating the flow rate over time. The measured water vapor permeability is shown in Fig. 4, and the permeability at a relative humidity of 15 RH% is shown in Table 1 and Fig. 7 below.

[0094] In addition, the water vapor (H2O) / nitrogen (N2) selectivity was calculated based on the permeation flow rate and composition of the membrane for a water vapor / nitrogen mixed gas (9 / 1=v / v). Specifically, a cellulose film was fixed and sealed in a cell dedicated to gas permeation experiments, and the relative humidity on the supply side and the permeation side was fixed at 0% as an initial condition. Subsequently, the temperature on the supply side was set to room temperature, and the relative humidity and nitrogen flow rate were controlled to allow the mixed gas from the supply side to continuously permeate through the membrane to the permeation side, while also enabling the measurement of the flow rate to proceed with the experiment. The water vapor permeability was calculated by calculating the flow rate over time and the humidity increasing as water vapor permeated through the cellulose membrane inside the cell according to humidity, and the water vapor (H2O) / nitrogen (N2) selectivity was calculated by dividing the nitrogen permeability obtained through GC analysis of the permeated gas, and is listed in Table 1 below.

[0096] [Example 1]

[0097] An aqueous solution was prepared by dissolving 5 g of methyl cellulose in 95 g of water, and the aqueous solution was cast onto a glass plate and dried in a drying oven at 35 ℃ for 2 days to produce a cellulose ether film with a thickness of 80 µm. After vacuum drying the cellulose ether film for an additional 1 hour, the film was immersed in 100 ml of methanol containing 5 g of maleic acid for 3 hours. The wet film was left in an oven at 170 ℃ for 10 minutes to perform an esterification reaction, thereby obtaining a cellulose ester film with a thickness of 80 µm. Subsequently, the cellulose ester film was immersed in methanol for 12 hours to perform solvent annealing, and then dried in a drying oven at 82.5 ℃ for 12 hours to finally obtain the cellulose film according to Example 1.

[0098] [Example 2]

[0099] An aqueous solution was prepared by dissolving 5 g of methyl cellulose (Sodium MC, Mw: 118,000 Da, DS (degree of ether substitution): 1.5~1.9) and 1.25 g of maleic acid in 95 g of water. The aqueous solution was cast onto a glass plate and dried in a drying oven at 35 ℃ for 2 days to produce a cellulose ether film with a thickness of 80 µm. The cellulose ether film was vacuum dried for an additional 1 hour, and then left in an oven at 170 ℃ for 2 hours to perform an esterification reaction, thereby obtaining a cellulose ester film with a thickness of 80 µm. Subsequently, the cellulose ester film was immersed in methanol for 12 hours to perform solvent annealing, and then dried in a drying oven at 82.5 ℃ for 12 hours to finally obtain a cellulose film according to Example 2.

[0100] [Comparative Example 1]

[0101] In Example 1 above, a cellulose ether film that did not undergo an ester reaction was prepared.

[0102] [Comparative Example 2]

[0103] In Example 1 above, a cellulose ester film was prepared without performing solvent annealing.

[0104] Tensile strength at break (dry) [MPa] Water vapor adsorption rate (75RH%) [%] Water vapor permeability (15RH%) [Barrer] Water vapor selectivity (30RH%, H2O / N2)[Barrer / Barrer] Comparative Example 1 62 14.9 100,000 1,200 Comparative Example 2 43 8.2 76,000 1,800 Example 1 75 9.9 210,000 1,700

[0105] As shown in Table 1 and Figures 2 to 7 above, it was confirmed that the cellulose film according to Example 1 exhibits excellent mechanical properties, such as superior tensile strength and elongation compared to Comparative Examples 1 and 2, and also exhibits excellent water vapor adsorption rate, permeability, and selectivity. Furthermore, while cracked and uneven films were produced using conventional technology, it was confirmed that when using the method for producing a cellulose film according to one embodiment using a low-temperature drying method, a uniform and large-area cellulose film that does not crack can be produced.

[0106] In addition, as shown in FIG. 2, it was confirmed that the crystallinity of the cellulose film according to Example 1 was improved by more than 1.5 times compared to Comparative Example 2, which did not undergo the solvent annealing process. In addition, as shown in FIG. 3, it can be confirmed that the hydrophilicity was effectively controlled by exhibiting a higher contact angle compared to Comparative Example 1, which was not treated.

[0107] In addition, looking at Fig. 4, it can be seen that in the case of Comparative Example 1, the tensile strength in the wet state in contact with water is about 43, which is more than 30% lower than the value (62) in the dry state, whereas in the case of Example 1, the tensile strength in the wet state in contact with water is about 66, which is only about 12% lower than the value (75) in the dry state.

[0108] In addition, as shown in Figures 5 and 6, the cellulose film according to Example 1 exhibited the highest hysteresis at 75% relative humidity and also showed superior water vapor adsorption behavior compared to Comparative Example 2, which did not undergo a solvent annealing process.

[0109] Above all, as shown in FIG. 7, the water vapor permeability of the cellulose film of Example 1 is significantly higher than that of Comparative Examples 1 and 2 over the overall relative humidity range, and in particular, as can be seen in Table 1 above, it was confirmed that the cellulose film of Example 1 exhibits significantly superior permeability and selectivity at a low relative humidity of 15%.

[0110] Through this, it was confirmed that the cellulose film according to one embodiment can exhibit excellent water vapor adsorption rate, permeability, and selectivity without a rapid degradation of mechanical properties, and can be applied not only to water vapor separation in low-humidity ranges such as exhaust gas, but also to a wide range of fields requiring dehumidification membranes through an easy film manufacturing process and economic advantages.

[0111] As described above, the present invention has been explained by specific details and limited embodiments; however, this is provided merely to aid in a more comprehensive understanding of the invention, and the invention is not limited to the above embodiments. Those skilled in the art can make various modifications and variations from this description.

[0112] Accordingly, the scope of the present invention is not limited to the described embodiments, and all things equivalent to or having equivalent variations to the claims set forth below, as well as the claims set forth below, shall be considered to fall within the scope of the concept of the present invention.

Claims

Claim 1 (a) a step of preparing a cellulose ether film by casting an aqueous solution in which a cellulose ether derivative is dissolved in water and low-temperature drying at a temperature of 40°C or lower; (b) a step of preparing a cellulose ester film by esterifying the cellulose ether film; and (c) a step of performing solvent annealing by impregnating the cellulose ester film with a methanol solvent; comprising a method for preparing a cellulose film. Claim 2 delete Claim 3 delete Claim 4 delete Claim 5 A method for manufacturing a cellulose film according to claim 1, further comprising the step of drying at a temperature ± 5℃ of the boiling point of the solvent after step (c). Claim 6 delete Claim 7 A method for manufacturing a cellulose film according to claim 1, wherein the aqueous solution further comprises a polyfunctional compound containing at least one carboxyl group. Claim 8 A method for manufacturing a cellulose film according to claim 7, wherein the polyfunctional compound contains at least one carboxyl group and at least one amino group. Claim 9 A method for manufacturing a cellulose film according to claim 1, wherein the esterification reaction is performed at a temperature of 150°C or higher. Claim 10 A method for manufacturing a cellulose film according to claim 1, wherein step (b) involves contacting a cellulose ether film with a reaction solution comprising a polyfunctional compound containing at least one carboxyl group and a solvent to perform an esterification reaction. Claim 11 A method for manufacturing a cellulose film according to claim 10, wherein the aqueous solution and the reaction solution each independently further comprise a polar solvent. Claim 12 In claim 1, the cellulose ether derivative is C 1-7 Alkyl cellulose, hydroxy C 1-7 Alkyl cellulose and carboxy C 1-7 A method for manufacturing a cellulose film which is one or more combinations selected from alkyl cellulose. Claim 13 A method for manufacturing a cellulose film according to claim 1, wherein the contact angle of the cellulose ester film with water is greater than that of the cellulose ether film. Claim 14 A cellulose film manufactured according to the method for manufacturing a cellulose film selected from any one of claims 1, 5 and 7 to 13. Claim 15 In claim 14, the film is a cellulose film having a breaking tensile strength of 60 MPa or more and an elongation of 10% or more, measured according to ASTM D882 under a thickness condition of 80 ± 2 μm. Claim 16 In claim 14, a cellulose film having a water vapor adsorption rate of 2% or more of a film with a thickness of 80±2㎛ at a relative humidity of 75%. Claim 17 In claim 14, a cellulose film having a thickness of 80±2㎛ at a relative humidity of 30% and a water vapor (H2O) / nitrogen (N2) selectivity of 1,500 or more. Claim 18 In claim 14, a cellulose film having a thickness of 80±2㎛ at a relative humidity of 15% and a water vapor permeability of 100,000 Barrer or more. Claim 19 A dehumidifying film comprising the cellulose film of claim 14.

Citation Information

Patent Citations

  • Modified cellulose ether film

    JP2004155805A

  • Membrane, method for manufacturing the same and water treatment device including the same

    KR1020130011899A

  • Separation membrane and method of preparing and using same

    US4527999A